A educação alimentar e nutricional e as práticas dos professores de educação física: uma possibilidade para escolas de Fortaleza - Nunes, Alexandra Régia Nobre Monteiro (2019)
The inclusion of Food and Nutrition Education (EAN) in the teaching and learning process in Physical Education classes, as a cross-curricular theme, was shown to be a strategy for achieving healthy student habits, because school is considered a privileged space for pedagogical actions in the perspective of the food theme and in the development of healthy life practices, as children and adolescents feed themselves, learn to give meaning to what they eat and spend a significant amount of time in the school environment. Therefore, the Food and Nutrition Education Framework for Public Policies (2012) defines EAN as a field of continuous and ongoing, transdisciplinary, intersectoral and multiprofessional knowledge and practice whose objective is the implementation of the autonomous and voluntary practice of healthy eating habits. The dissertation investigated how physical education teachers conceived healthy eating and how these teachers developed activities to promote healthy eating based on their teaching practices, as well as the resources used and their difficulties and facilities to deal with the issue. The research was of a qualitative nature, having as data collection technique the semi-structured interview and participant observation carried out with seven Physical Education teachers, in four municipal public schools in Fortaleza. The qualitative data were analyzed according to the fundamentals of Depth Hermeneutics with socio-historical analysis; formal or discursive analysis; and interpretation / reinterpretation. The results indicated that Physical Education teachers have the knowledge and interest to work on the theme of healthy eating, they approach this theme in their classes, in different ways, but they have presented some difficulties and weaknesses in relation to the structural and financial availability of the school and students to perform certain important activities related to the topic. Therefore, it was evidenced that Physical Education teachers can work on the theme of healthy eating in a transversal way, using methodological strategies that are possible for students, taking into account their values, their cultures, healthy foods easily accessible and the autonomy of the student to take care of his / her own health.